2017
DOI: 10.1017/s0021859617000673
|View full text |Cite
|
Sign up to set email alerts
|

Ingestive behaviour and forage intake responses of young and mature steers to the vertical differentiation of sugarcane in pen and grazing studies

Abstract: SUMMARYSugarcane is an important forage resource in sub-tropical and tropical areas as it is used during the winter or dry season when the growth rate of pastures is significantly reduced. The current research study assessed the effect of four vertical sections of sugarcane in a pen trial and the level of sugarcane utilization in a grazing trial on the ingestive behaviour and forage intake of two age groups of steers (1 and 2 years old). The pen trial was comprised of two simultaneous 4 × 4 balanced Latin squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
2
10
0
3
Order By: Relevance
“…It is well known from previous studies that beef and dairy cattle graze pastures in strata, and herbage quality declines from the top to the bottom of the swards (Ungar and Ravid 1999;Benvenutti et al 2016Benvenutti et al , 2017Ison et al 2018). These studies found that, when grazing pressure increased, cattle were forced to graze forage in the lower strata which was of lower quality and as a result diet quality and animal performance declined.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known from previous studies that beef and dairy cattle graze pastures in strata, and herbage quality declines from the top to the bottom of the swards (Ungar and Ravid 1999;Benvenutti et al 2016Benvenutti et al , 2017Ison et al 2018). These studies found that, when grazing pressure increased, cattle were forced to graze forage in the lower strata which was of lower quality and as a result diet quality and animal performance declined.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known from previous studies that beef and dairy cattle graze pastures in strata, and herbage quality declines from the top to the bottom of the swards (Ungar and Ravid 1999;Benvenutti et al 2016Benvenutti et al , 2017Ison et al 2018). These studies found that, when grazing pressure increased, cattle were forced to graze forage in the lower strata which was of lower quality and as a result diet quality and animal performance declined.…”
Section: Short Communicationmentioning
confidence: 99%
“…En el Renopa, la proporción de forraje remanente no pastado fue aproximadamente 11%, lo que permite que el consumo voluntario y por tanto la ganancia diaria de peso no sean limitados antes del cambio de potrero, como se observó en los estudios anteriores (Benvenutti et al 2016;2017). El mayor consumo voluntario de los animales en el sistema Renopa es debido al mejor acceso al estrato superior de la gramínea (= hojas con valor nutritivo más alto) por los animales.…”
Section: Ganancia De Peso Vivounclassified
“…No obstante esta estrategia es limitada por el hecho que la altura residual a la cual el consumo de forraje y la respuesta animal decrecen depende no solo de la especie de pastura sino también de la altura al comienzo del pastoreo (Benvenutti et al 2016;2017). Benvenutti et al (2016;2017) en pasturas del pasto Jesuita Gigante (Axonopus catarinensis) en un sistema de rotación y en caña de azúcar, encontraron que aplicando el criterio del forraje remanente no-pastado (Renopa) mejoró el consumo de forraje por bovinos en pasturas con diferentes alturas. En estos trabajos se encontró que al comienzo del periodo de ocupación los animales alcanzaron el mayor nivel de consumo diario de forraje especialmente en el estrato superior de hojas de la pastura.…”
Section: Introductionunclassified
See 1 more Smart Citation